Archaeology and Languages: Breaking New Ground - Renfrew, Colin (Pontificia Universidad Católica del Perú, 2012)
Questions of the relationships between archaeology and language have long focused on problems of the Indo-European language family. This chapter considers general processes of archaeological and linguistic change with a special focus on language replacement. Here the model of agriculture/language dispersal is particularly significant. The potential contributions of archaeogenetics are also considered.